Publisher Correction: Engineering bacterial vortex lattice via direct laser lithography. Issue 1 (December 2018) - Nishiguchi, Daiki; Aranson, Igor; Snezhko, Alexey; Sokolov, Andrey
The original version of this Article contained errors in Fig. 2. In Fig. 2d, the label below the blue circle incorrectly read "S i, a (t ) < 0" and should have read "S i, a (t ) > 0". Furthermore, the sequence of labels on the side of the bottom three figures panels in Fig. 2d from top to bottom incorrectly read "S 9, 70 > 0, S 9, 70 > 0, S 9, 70 < 0", and should have read "S 9, 70 < 0, S 9, 70 > 0, S 9, 70 < 0". Finally, in the legend to Fig. 2, the scale bar size description "Scale bar: 100μm" was incorrectly placed in the description of panel c, and should have been placed in the description of panel d. These errors have been corrected in both the PDF and HTML versions of the Article.